Shaping well-defined noble-metal-based nanostructures for fabricating high-performance electrocatalysts: advances and perspectives. Issue 10 (1st August 2019) - Yin, Hai-Jing; Zhou, Jun-Hao; Zhang, Ya-Wen
Abstract : This review highlights recent advances in shaping protocols and structure-activity relationships of noble-metal-based catalysts with well-defined nanostructures in electrochemical reactions. Abstract : Electrocatalytic reactions have received widespread attention in the recent decades because of their importance in environmental protection and energy storage and utilization, involving fuel cells, electrolysis of water, and electrochemical reduction of carbon dioxide and nitrogen. Among the various nanocatalysts, noble-metal-based ones (containing Ru, Rh, Ir, Pd, Pt, Ag, and Au) exhibit superior performances in most electrocatalytic reactions for their higher catalytic activity and stability as compared to nonnoble-metal-based ones. Currently, the atomic-scale nanoengineering of noble-metal-based electrocatalysts has been demonstrated to be an efficient and robust approach to address specific problems either in catalytic activity/selectivity or durability in a given electrochemical reaction, through understanding the structure–activity relationship of catalysts at the molecular level. In this review, we summarize the progresses made in noble-metal-based nanocatalysts toward some important electrochemical reactions of small-molecule activation ( e.g., O2, H2, H2 O, CH3 OH, CO2, and N2 ), which involve three aspects: (1) how to synthesize noble-metal-based electrocatalysts with well-defined nanostructures; (2) how to tune the catalytic performance of electrocatalytic reactions; and (3) how to determine the optimal surface structure of catalysts according to the understanding of the structure–activity relationship. Further, we provide prospects for the sustainable development of this cutting-edge field.